Strengthening MSMEs in Tabanan through Beaded Accessory Craft: Product Design Development and Digital Marketing Assistance - DEWI, I Gusti Ayu Agung Istri Sari; PURNAMAWATI, Ida Ayu Putu Santi; PUTRI, Sukmasari Triana Gita (Community Services: Sustainability Development, 2025)
This community service program was conducted to support the development of micro, small, and medium enterprises (MSMEs), specifically Anasera, a beaded accessory craft business located in Tabanan Regency, Bali. Anasera sells its handmade products through offline art shops in the Tanah Lot tourist area but faces challenges in product design innovation and lacks an effective digital marketing strategy. These limitations reduce the business's ability to compete and grow, especially in the increasingly digital marketplace. The program focused on two main areas: (1) improving product design by providing training on color composition, trend adaptation, and uniqueness in handmade accessories, and (2) enhancing digital marketing skills through workshops on content creation, the use of social media platforms, and basic e-commerce management. After the implementation, Anasera demonstrated improved product presentation, created engaging promotional content, and began utilizing digital platforms to reach a wider audience. This initiative highlights the importance of combining creative design development with digital marketing to empower local MSMEs, particularly in tourism-driven areas, to improve their sustainability and competitiveness in both offline and online markets.